Distribution and environmental risk assessment of microplastics in continental shelf sediments in the southern East China Sea: A high-spatial-resolution survey. (April 2022) - Li, Zhaozhao; Liu, Yandong; Zhang, Dahai; Feng, Lijuan; He, Xingliang; Duan, Xiaoyong; Li, Xianguo; Xie, Huixiang
Abstract: We report a high-spatial-resolution study on the distributions, characteristics, and environmental risks of microplastics in surface sediments of the southern East China Sea. Microplastics were omnipresent in the sediments (concentration range: 53.3–246.7; mean: 138.4 particles/kg dry-weight sediment) and enriched in nearshore areas close to urban centers relative to lower offshore concentrations. The microplastics identified were dominated by polyethylene (41.2%) and polyethylene terephthalate (19.9%) in polymer type, fibers (45.8%) and fragments (40.3%) in shape, 0.1–0.5 mm (61.0%) in size, and black (52.0%) in color. The benthic environment experienced low to moderate microplastic pollution, with polyvinylchloride exhibiting the highest ecological risk index. The high-resolution sampling revealed highly diverse polymer types and strongly patchy distributions of microplastic abundance and pollution indices in sediments. Results from this study imply that complex physical, biological, and topographic interactions control the distribution of microplastics and the associated environmental risks in coastal sediments. Highlights: Highest spatial-resolution study of sedimentary microplastics in China's coastal seas Microplastics are ubiquitous in sediments of the southern East China Sea. Fibrous and fragment, polyethylene and polyethylene terephthalate are dominant. Pollution load index indicates mild microplastic contamination. Polyvinyl chloride poses the highest ecological risk.